2021
DOI: 10.1148/radiol.2021201740
|View full text |Cite
|
Sign up to set email alerts
|

Oncologically Relevant Findings Reporting and Data System (ONCO-RADS): Guidelines for the Acquisition, Interpretation, and Reporting of Whole-Body MRI for Cancer Screening

Abstract: number of examinations being performed in patients with known cancers, an international multidisciplinary expert panel of radiologists and a geneticist with subject-specific expertise formulated technical acquisition standards, interpretation criteria, and limitations of whole-body MRI for cancer screening in individuals at higher risk, including those with cancer predisposition syndromes. The Oncologically Relevant Findings Reporting and Data System (ONCO-RADS) proposes a standard protocol for individuals at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…29 We considered the fact that in some cases clinical follow-up was longer than wb-MRI and sFLC-ratio assessment might have introduced a bias as described and investigated in Data S1; however, the additional analysis revealed that this had no relevant effect on the results of this study. Availability and cost of wb-MRI is still hindering the largescale application of wb-MRI in many healthcare systems, but over the last decade wb-MRI plays an increasing role across different oncological entities, [38][39][40] and compared to the high costs of modern MM treatment the costs for wb-MRI are comparably low. While heterogeneity in MRI acquisition and interpretation might be considered challenges for wb-MRI, there is an ongoing process of standardization of acquisition and interpretation of wb-MRIs, as for example the recent introduction of the MY-RADS criteria.…”
Section: Discussionmentioning
confidence: 99%
“…29 We considered the fact that in some cases clinical follow-up was longer than wb-MRI and sFLC-ratio assessment might have introduced a bias as described and investigated in Data S1; however, the additional analysis revealed that this had no relevant effect on the results of this study. Availability and cost of wb-MRI is still hindering the largescale application of wb-MRI in many healthcare systems, but over the last decade wb-MRI plays an increasing role across different oncological entities, [38][39][40] and compared to the high costs of modern MM treatment the costs for wb-MRI are comparably low. While heterogeneity in MRI acquisition and interpretation might be considered challenges for wb-MRI, there is an ongoing process of standardization of acquisition and interpretation of wb-MRIs, as for example the recent introduction of the MY-RADS criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Impediments to widespread WB-MRI implementation include variation in machine protocol and acquisition parameters, radiologist experience in interpretation, and lack of uniform reporting structure. Petralia et al recently published guidelines- Oncologically Relevant Findings Reporting and Data System (ONCO-RADS)-- to address some of these concerns, emphasizing a standard framework for categorizing abnormal findings so that risk stratification for malignancy can be better communicated [15] . For WB-MRI, younger children need to be sedated to ensure images are not degraded by motion artifacts [16] .…”
Section: Pet/ct and Whole Body-mrimentioning
confidence: 99%
“…The categorical systems reported showed, however, a high heterogeneity, with four studies using a binary system [ 18 , 25 , 32 , 34 ], four studies a three-category system [ 23 , 30 , 36 , 37 ], three a four-category system [ 19 , 27 , 31 ], one a five-category system [ 24 ]; one last study used a six-category system for both patients with cancer predisposition syndromes and asymptomatic subjects of the general population [ 21 ]. The recently published Oncologically Relevant Findings Reporting and Data System (ONCO-RADS) guidelines [ 57 ] represent a comprehensive effort towards the standardisation of WB-MRI reporting in the setting of cancer screening. These guidelines provide a template for structured reporting, as well as a five-category classification system for data collection and a systematic approach for the communication and management of abnormal findings.…”
Section: Imaging Acquisition Protocolmentioning
confidence: 99%